Iqbal and modern Islamic educationists, part 1: The perceived aims and objectives of education – A comparative analysis. - Ali, Abid; Hussien, Suhailah (2020)
Iqbal views the schooling as well as the Madrassah systems devoid of developing a dynamic Muslim required for the renaissance of Ummah. With this realization, many Islamic educationists in Pakistan have established. Islamic schools in Pakistan. The question is whether their models are dynamic enough to create such Muslims? This research probes into the perceptions and practices of ten Islamic school educationists in Pakistan. It also probes and clearly elaborates Iqbal’s educational directives, and finally does a comparative analysis of Iqbal’s directives with the Islamic educationists’ perceptions and practices. Exploring Iqbal’s educational thought includes qualitatively drawing hermeneutical interpretations from Iqbal’s two Persian anthologies of Asrar i khudi (Secrets of the Self), and Ramooz i bikhudi (Mysteries of Selflessness). Thematic data analysis was used to draw the aims and objectives for education from Iqbal’s said works. It was discovered that though the Islamic educationists carried some visions of education from Islamic perspective, they were largely following contemporary secular frame work of education in attempting to achieve these objectives. The contemporary schooling framework has been severely critiqued by Iqbal and is deplored by many educationists in the west as well for its ineptness to confirm with child’s learning psychology. This project was undertaken as my doctoral research and is presented in two parts. The first part elaborates the aims and objectives as conceived by these Islamic educationists, and as derived from Iqbal’s educational philosophy. The second part of this paper will elaborate the practices of these educationists with Iqbal’s educational directives.